2009
DOI: 10.1002/lary.20727
|View full text |Cite
|
Sign up to set email alerts
|

Combined antegrade and retrograde esophageal dilation for head and neck cancer‐related complete esophageal stenosis

Abstract: CARD was safe and effective. Intraoperative patency was achieved in 91% of patients. Eighty percent resumed oral intake. The majority of patients had their GTs removed and resumed a soft or regular diet. Dilation failure was associated with laryngeal, pharyngeal, and excessively long esophageal stenosis, often resulting from radionecrosis. Complications were minor. CARD should be considered before relegating patients with complete esophageal stenosis to chronic GT dependence or subjecting them to laryngopharyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 45 publications
3
45
3
Order By: Relevance
“…A recent meta-analysis [7] reported an estimated overall clinical success rate per patient (with a post-chemotherapy and RT or RT alone stricture) of 72.9% (95% CI 65.7-80.1%), with data suffering from significant heterogeneity as success was defined by resolution or improvement of different dysphagia scales. Previous findings stated that a soft/ normal diet may be achieved in > 70% [12,16,23,28] compared to 60% reported in our cohort. On the other hand, our dysphagia improvement perception rate was 58.3% Fig.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…A recent meta-analysis [7] reported an estimated overall clinical success rate per patient (with a post-chemotherapy and RT or RT alone stricture) of 72.9% (95% CI 65.7-80.1%), with data suffering from significant heterogeneity as success was defined by resolution or improvement of different dysphagia scales. Previous findings stated that a soft/ normal diet may be achieved in > 70% [12,16,23,28] compared to 60% reported in our cohort. On the other hand, our dysphagia improvement perception rate was 58.3% Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…excellent and followed the one previously described by Francis et al [22]. Moreover, our independence of gastrostomy tube rate was better than in most previous studies [22,23,28]. We found that initial lumen diameter, number of dilations, and nonrecurrent strictures were predictive factors for overall efficacy.…”
Section: Discussionsupporting
confidence: 27%
“…We and other authors have reported bidirectional oesophageal dilatation or retrograde endoscopically assisted oesophageal dilatation to be safer and with higher success rates than the standard anterograde flexible/rigid oesophagoscopy [6][7][8][9][10][11][12]. This technique is feasible in patients with PEG tubes.…”
Section: Introductionmentioning
confidence: 76%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The largest retrospective study, recently reported by a surgical group, presented the results of ELR in 45 patients. 22 That report included 5 patients previously reported. 5 The techniques for ELR are similar, but there are major differences in the before-procedure and afterprocedure programs and in long-term dilation for lumen maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…During this period there were 19 reports (excluding abstracts) for a total of 102 successful lumen restorations out of 125 attempts in 111 patients. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Sixty-five of 102 patients with available oral intake data reported restoration of the ability to swallow soft to regular consistency foods.…”
Section: Introductionmentioning
confidence: 99%